Surface modification of polypropylene non-woven fabric for improving its hydrophilicity. (2nd November 2018) - Long, Xiaoyun; He, Lifen; Zhang, Yan; Yu, Shufa; Ge, Mingqiao
ABSTRACT: In this study, nano-silica thin films were deposited on the surface of polypropylene (PP) non-woven fabric (NWF) by reactive magnetron sputtering with a mixture of argon and oxygen gases to improve the hydrophilicity of the materials. The effects of process parameters, including oxygen gas concentration, treatment time, and density of the sample on the resulting hydrophilicity of the fabricated product were measured in terms of relative weight increase caused by the adsorption of water and water contact angle. The results indicated that the PP NWF modified by reactive magnetron sputtering at an oxygen gas concentration of 40%, a treatment time of 20 min, and a density less than 500 g/m 2 showed improved hydrophilicity. In addition, the surface morphology and chemical composition of the treated samples were examined by scanning electron microscopy and X-ray photoelectron spectrometry. It was determined that the silicon dioxide nanoparticles were evenly deposited on the surface of fibres.